2020
DOI: 10.1101/2020.10.16.342923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial phenotypes in purified human immune cell subtypes and cell mixtures

Abstract: How mitochondria functionally differ between immune cell subtypes, between the sexes, across ages, and whether they dynamically change over time has not been characterized. Here we deploy a high-throughput mitochondrial phenotyping platform to define cell-type specific mitochondrial features in circulating immune cell subtypes. In women and men spanning four decades of life, we find that mitochondrial content, mitochondrial DNA copy number (mtDNAcn), and respiratory chain enzymatic activities vary by up to 3.5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 98 publications
0
10
1
Order By: Relevance
“…This increase was linked to oxidative stress responses and suggested as a possible mechanism to compensate for defects in mitochondria retaining mutated mtDNA [ 38 ]. Other previous studies have consistently reported an age-related decline in mtDNA copy number (mtDNAcn) [ 39 , 40 , 41 , 42 ], but these results are confounded by mixed cell samples and contamination from platelets, which inflate mtDNAcn and decline in number with age [ 43 ]. A study specifically examining peripheral blood mononuclear cells observed a positive correlation between mtDNAcn and age [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase was linked to oxidative stress responses and suggested as a possible mechanism to compensate for defects in mitochondria retaining mutated mtDNA [ 38 ]. Other previous studies have consistently reported an age-related decline in mtDNA copy number (mtDNAcn) [ 39 , 40 , 41 , 42 ], but these results are confounded by mixed cell samples and contamination from platelets, which inflate mtDNAcn and decline in number with age [ 43 ]. A study specifically examining peripheral blood mononuclear cells observed a positive correlation between mtDNAcn and age [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies have consistently reported an age-related decline in mtDNA copy number (mtDNAcn) [ 39 , 40 , 41 , 42 ], but these results are confounded by mixed cell samples and contamination from platelets, which inflate mtDNAcn and decline in number with age [ 43 ]. A study specifically examining peripheral blood mononuclear cells observed a positive correlation between mtDNAcn and age [ 43 ]. This may be used by cells as a compensatory upregulation to counteract the loss of functionally intact mitochondria with age [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mtDNAcn has been suggested as a biomarker for aging because several studies of peripheral blood have reported an inverse correlation between age and mtDNAcn (Fries et al, 2017; Mengel-From et al, 2014). However, more recent studies demonstrated that the inverse correlation is likely caused by unaccounted age-related changes of cell type proportions in the blood (Moore et al, 2018; Rausser et al, 2021). In our study, we found no association between mtDNAcn and age or sex in the studied brain regions when we adjusted for pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration for blood-based bioenergetics is selecting an appropriate cell type to use for respirometry experiments and whether mixed cell populations, such as PBMCs, are suitable samples for respirometry. Rausser et al used a high-throughput mitochondrial phenotyping platform to compare PBMCs to leukocyte subtypes from the same individual [135]. They show large functional differences in both mitochondrial content and respiratory chain enzymatic activity between immune cell subtypes.…”
Section: Considerations For Utilizing Circulating Blood Cells For Respirometry Studiesmentioning
confidence: 99%